215k views
5 votes
Let x = a + bi and y = c + di and z = f + gi

Which statements are true? Check all of the boxes that apply.

x + y = y + x

(x × y) × z = x × (y × z)

x – y = y – x

(x + y) + z = x + (y + z)

(x – y) – z = x – (y – z)

User TasosZG
by
5.1k points

2 Answers

4 votes

x + y = y + x … … … True, since addition is commutative.

(xy) • z = x • (yz) … … … True, since multiplication is associative.

x - y = y - x … … … False. Suppose y = 0. Then the claim is x = -x, which is only true if x = 0.

(x + y) + z = x + (y + z) … … … True, since addition is associative.

(x - y) - z = x - (y - z) … … … False. If x = y = 0, then the claim is -z = z, which only holds for z = 0.

User Amrik
by
5.0k points
6 votes

Answer:

A,B,D

Explanation:

short version of above.

User Strange Quark
by
4.9k points